Catalytic valorization of lignocellulosics: from bulk biofuels to value‐added chemicals. (26th January 2021) - Zhang, Shen; Yu, Youfang; Sheng, Kuichuan; Liu, Jianglong; E, Shuang; Jin, Caidi; Xu, Zenghua; Zhang, Ximing
Abstract: Lignocellulose is a key starting material for the production of biofuels, biochemicals, and biomaterials. This review discusses various catalytic systems, including homogeneous and heterogeneous catalytic systems, for biomass valorization. Different strategies of biomass‐derived catalyst systems for value‐added chemicals are evaluated. Novel strategies for using biomass‐derived carbon‐based catalysts are proposed as a potential way to make the valorization process economically viable. This review also provides a comprehensive assessment of the fabrication of biomass‐derived carbon as catalytic support for biorefinery applications and discussion about mechanism of the synergistic catalytic effect between the biochar and catalyst. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd